Pelatihan Pembuatan Teh Dan Permen Dari Bunga Telang Pada Ibu-Ibu PKK Dusun Losari Desa Kwangsan Jumapolo Karanganyar - Rahmadani, Triwulan; Setiani, Siti; Gita Cahyani, Putri Indah; Rastanti, Heni; Putra, Ardian Prima (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2024)
This training also aims to empower the community to process butterfly pea flowers into tea and sweets, an initiative that aims to improve health and welfare at the community level. Through education, training and skills development, the community is ready to realize the potential of telang flowers for health and process them into value-added products such as tea and candy. These steps include adding information about the benefits of butterfly pea flowers for health and the production process of tea and sweets. Through a series of trainings, this approach aims to ensure that the community, especially PKK women in Losari Hamlet, Kwangsan Village, Jumapolo, Karanganyar, know the benefits of telang flowers, not only as animal feed. The main focus is only increasing the value of telang flowers for animal feed, knowing the health benefits and expanding entrepreneurial skills. The results of this program are expected to increase community participation in the use of telang flowers and the community will also become more aware that plants which were originally only used for animal feed actually have many benefits for body health and are also sustainable and sustainable. . economically empowering domestic businesses.